A whole-food, plant-based program in an African American faith-based population - Nyong, Faith A.; Barnett, Ted D.; Garver, Beth; Dewhirst, Maria; Pollock, Bruce; Friedman, Susan M. (Frontiers in Nutrition, 2023)
Background - The African American (AA) population is disproportionately impacted by chronic disease as well as many of the leading causes of preventable death, including hypertension, obesity, heart disease, stroke, and type 2 diabetes. In the AA community of Kane County, Illinois, the incidence of chronic disease is particularly high. A standardized Zoom-based group program that gives participants the knowledge, skills, and support to adopt a whole-food plant-based diet has been shown to rapidly improve health. We analyzed the results of a cohort of participants, to determine whether this program was effective in an AA community with a high burden of chronic illness. Methods - Participants were recruited from a network of 12 AA churches in Illinois to participate in Rochester Lifestyle Medicine Institute’s “15-Day Whole-Food Plant-Based (WFPB) Jumpstart” program. The medically-facilitated 15-Day Jumpstart program provided WFPB nutrition education, coaching, and cooking demonstrations during seven one and two-hour Zoom sessions. Participants underwent pre- and post-metabolic screenings to assess for changes in their weight, vital signs, blood sugar, and cholesterol measurements. Changes in diet, biometrics, and patient-centered outcomes from baseline to the end of the program were assessed via paired t-tests. Results - 21 AA adults participated. Ten of 16 who provided results had hypertension, 5 had diabetes, 5 had pre-diabetes, and 5 had hyperlipidemia. Participants ate more vegetables (median 2 servings at baseline vs. 3 during the program), greens (1 vs. 3), fruit (2 vs. 3), whole grains (1 vs. 2), and legumes (1 vs. 2). They decreased their consumption of meat, eggs and dairy, added fat, processed foods, and high-fat plant foods (p < 0.05 for each comparison). Participants reported significantly better energy (median 5 at baseline vs. 9 during the program, on a 10-point scale), sleep (7 vs. 8.5), and mood (8 vs. 9). Average weight loss was 5.8 pounds (199.9 to 194.1, p< 0.001), systolic blood pressure dropped from 129.7 to 119.9 (p =0.02), and total cholesterol dropped from 185.1 to 147.9 (p < 0.001). All participants who provided data reported an intent to continue eating at least a partially WFPB diet following the program.